(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate clinical results of primary repair with silicone tube intubation after traumatic injury of lacrimal canalicular system. Materials and Methods: Fifteen patients applied to ophthalmology clinic at Afyonkarahisar Health Sciences University between January 2010 and May 2020 with traumatic injury of lacrimal canaliculi were included in the study. Data including the patients’ demographic characteristics, causes of injury, time between trauma and surgery, surgical technique, post-operative time of silicone tube removal, post-operative follow-up period, and anatomical as well as functional outcomes were retrieved from the patients’ clinical records. Results: Mean age of the patients was 26±22.5 (3 to 70 years) years (13 males, 2 females). Ten patients (66.6%) had blunt trauma, whereas penetrating injury was detected as causative factor of trauma in five patients (33.3%). Twelve patients (80%) had isolated lower canalicular injury, two (13.3%) had upper canalicular injury, and the remaining one (6.7%) had both lower and upper canalicular injury. The primary surgical repair with silicone tube intubation was performed in all patients. Twelve patients (80%) had successful anatomical and functional outcomes. Post-operative ptosis was detected in one patient. Although two patients (13.3%) underwent re-operation at another center, status their functional success could not be acquired. Conclusion: Annular intubation with the silicon tube can be used as an effective method for providing anatomical and functional integrity of the drainage system after blunt and / or penetrating traumatic injuries of the lacrimal canaliculi.